Pengaruh Key Opinion Leader Terhadap Keputusan Pembelian Produk Kesehatan Ikan [The Influence of Key Opinion Leaders on Fish Health Product Purchase Decisions] - Poniman (Universitas Pelita Harapan, 2025)
The development of digital technologies and social media has changed the way fish farmers access information and purchase valuable fish health products. However, there is no research on marketing to the fish farming community. With the spread of the internet in Indonesia, key opinion leaders (KOLs) have become an important marketing strategy to effectively reach the fishing community. The aim of this study is to analyze the influence of KOLs on fish farmers’ decisions to purchase health products in Sumatra and Java. It examines three broad dimensions of KOLs (relevance, scope, and value of involvement) and four dimensions of purchase decisions (product selection, brand, location, and payment method). A quantitative survey was conducted among 76 fish farmers in Sumatra and Java Island. The survey instrument showed good validity and reliability (Cronbach’s alpha > 0.9) and multiple regression analysis showed that KOLs significantly influenced purchase decisions (R = 0.853, R2 = 0.727). The dimensions of Reach and Rate of Engagement had the largest and most significant impact on purchasing behavior. This strategy is strongly recommended as a viable approach to increase the effectiveness of sustainable fish product promotion in the Indonesian fish farming industry. Abstrak Bahasa Indonesia: Perkembangan teknologi digital dan media sosial telah mengubah cara petani ikan mengakses informasi dan membeli produk kesehatan ikan yang memiliki nilai market yang besar namun belum ada penelitian terkait bidang pemasaran terkait komunitas petani ikan. Dengan meningkatnya penggunaan internet di Indonesia, Key Opinion Leader (KOL) telah menjadi strategi pemasaran yang penting untuk menjangkau komunitas petani ikan secara efektif. Penelitian ini bertujuan untuk menganalisis pengaruh KOL terhadap keputusan pembelian produk kesehatan ikan oleh petani ikan di Sumatera dan Jawa. Penelitian ini mengkaji tiga dimensi utama KOL (relevansi, jangkauan dan nilai keterikatan) dan empat dimensi keputusan pembelian (pemilihan produk, merek, lokasi dan metode pembayaran). Survei kuantitatif dilakukan terhadap 76 responden ikan di Pulau Sumatera dan Jawa. Instrumen survei menunjukkan validitas dan reliabilitas yang baik (Cronbach’s Alpha > 0,9), dan analisis regresi berganda menunjukkan bahwa KOL secara signifikan memengaruhi keputusan pembelian (R = 0,853, R² = 0,727). Dimensi jangkauan dan nilai keterikatan memiliki dampak terbesar dan signifikan terhadap perilaku pembelian. Strategi ini sangat direkomendasikan sebagai pendekatan berkelanjutan dalam industri perikanan Indonesia untuk meningkatkan efektivitas promosi produk kesehatan ikan.